The effects of dual courts in brazilian antitrust law Brazilian antitrust law (Revista do Tribunal Regional Federal da 3ª Região, 2014)
Considering that Article 5, XXXV of the Federal Constitution establishes the fundamental guarantee of the non-appealability of the Judiciary's control over any injury or threat to the right, instituting the duality of instances in the Brazilian legal system, several questions arise about the reviewability of administrative decisions by the Judiciary. Although there is not much disagreement about the possibility of this review in the context of the judicial process, doubts arise about the limits of the Judiciary's action, in other words, whether the control can be broad or restricted to certain aspects of the administrative act. The issue is especially relevant given the prominence that the Administrative Council for Economic Defense (CADE) has gained recently and its more combative approach to the defense of competition, a system that gained new contours after the enactment of Law No. 12,529/2012, especially acts of conduct, which are more commonly brought to the attention of the Judiciary, compared to acts of concentration. As a result, the tendency is for a greater number of cases involving decisions handed down by CADE to reach the courts for analysis and control. It is therefore important to study the limits of judicial action, given the special characteristics of administrative action in these specific cases.
Keywords: Law no. 12.529/2012; CADE; antitrust law; reviewability of administrative decisions; judicial limits